No signal intensity increase in the dentate nucleus on unenhanced T1-weighted MR images after more than 20 serial injections of macrocyclic gadolinium-based contrast agents - Radbruch, Alexander; Haase, Robert; Weberling, Lukas D.; Vollmuth, Philipp; Wick, Wolfgang; Bendszus, Martin (Radiology, 2017)
PurposeTo determine the effect of more than 20 serial injections of macrocyclic gadolinium-based contrast agents (GBCAs) on the signal intensity (SI) of the dentate nucleus (DN) on unenhanced T1-weighted magnetic resonance (MR) images.Materials and MethodsIn this retrospective, institutional review board-approved study, 33 patients who underwent at least 20 consecutive MR imaging examinations (plus an additional MR imaging for reference) with the exclusive use of macrocyclic GBCAs gadoterate meglumine and gadobutrol were analyzed. SI ratio differences were calculated for DN-to-pons and DN-to-middle cerebellar peduncle (MCP) ratios by subtracting the SI ratio at the first MR imaging examination from the SI ratio at the last MR imaging examination. One-sample t tests were used to examine if the SI ratio differences differed from 0, and Bayes factors were calculated to quantify the strength of evidence for each test.ResultsPatients underwent a mean of 23.03 ± (standard deviation) 4.20 GBCA administrations (mean accumulated dose, 491.21 mL ± 87.04 of a 0.5 M GBCA solution) with an average of 12.09 weeks ± 2.16 between every administration. Both ratio differences did not differ significantly from 0 (DN-to-pons ratio: −0.0032 ± 0.0154, P = .248; DN-to-MCP ratio: −0.0011 ± 0.0093, P = .521), and one-sided Bayes factors provided substantial to strong evidence against an SI ratio increase (Bayes factor for DN-to-pons ratio = 0.09 and that for DN-to-MCP ratio = 0.12).ConclusionThe study indicates that 20 or more serial injections of macrocyclic GBCAs administered with on average 3 months between each injection are not associated with an SI increase in the DN.© RSNA, 2016